Under the map of Germany : nationalism and propaganda, 1918-1945 - Herb, Guntram Henrik, 1959- (Routledge, 1997)
Using extensive, previously undiscovered archival documentation, the author provides an analysis of the history and techniques of nationalist mapping in inter-War Germany and challenges the belief that national self-determination is a just cause.